Sovereignty, wellbeing and cultural connectivity in the Northwest Territories: In conversation with Robert Voudrach - McCartney, Shelagh (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2026)
As part of this special issue on northern housing and Indigenous homemaking, we are honoured to include an interview with Robert Voudrach, a respected Inuvialuit leader and community advocate. Voudrach has built a career spanning trades, construction management, and senior housing-development roles, including leadership positions within the Northwest Territories Housing Corporation and the Inuvialuit Regional Corporation–transitioning to contribute to public policy through his two term long role on the National Housing Council, where he advises the federal government on housing issues affecting Northern and Indigenous communities. Voudrach’s perspective is grounded in lived experience of northern housing and its intersection with land, culture, and self-determination. In preparing this piece, Voudrach met with Shelagh McCartney for a conversation about his experiences with housing and home. Though Voudrach and McCartney had only met once previously, they connected on shared beliefs in the importance of partnerships grounded in mutual learning, and the link between housing and community wellbeing. Voudrach’s reflections contribute to the issue’s broader aim of understanding housing not merely as shelter, but as a vital nexus for sovereignty, wellbeing, and cultural continuity in the North.